Extracellular Vesicles-mediated recombinant IL-10 protects against ascending infection-associated preterm birth by reducing fetal inflammatory response - Kammala, Ananth Kumar; Mosebarger, Angela; Radnaa, Enkhtuya; Rowlinson, Emma; Vora, Natasha; Fortunato, Stephen J.; Sharma, Surendra; Safarzadeh, Melody; Menon, Ramkumar (Frontiers in Immunology, 2023)
Background Fetal inflammatory response mediated by the influx of immune cells and activation of pro-inflammatory transcription factor NF-κB in feto-maternal uterine tissues is the major determinant of infection-associated preterm birth (PTB, live births < 37 weeks of gestation). Objective To reduce the incidence of PTB by minimizing inflammation, extracellular vesicles (EVs) were electroporetically engineered to contain anti-inflammatory cytokine interleukin (IL)-10 (eIL-10), and their efficacy was tested in an ascending model of infection (vaginal administration of E. coli) induced PTB in mouse models. Study design EVs (size: 30-170 nm) derived from HEK293T cells were electroporated with recombinant IL-10 at 500 volts and 125 Ω, and 6 pulses to generate eIL-10. eIL-10 structural characters (electron microscopy, nanoparticle tracking analysis, ExoView [size and cargo content] and functional properties (co-treatment of macrophage cells with LPS and eIL-10) were assessed. To test efficacy, CD1 mice were vaginally inoculated with E. coli (1010CFU) and subsequently treated with either PBS, eIL-10 (500ng) or Gentamicin (10mg/kg) or a combination of eIL-10+gentamicin. Fetal inflammatory response in maternal and fetal tissues after the infection or treatment were conducted by suspension Cytometer Time of Flight (CyTOF) using a transgenic mouse model that express red fluorescent TdTomato (mT+) in fetal cells. Results Engineered EVs were structurally and functionally stable and showed reduced proinflammatory cytokine production from LPS challenged macrophage cells in vitro. Maternal administration of eIL-10 (10 µg/kg body weight) crossed feto-maternal barriers to delay E. coli-induced PTB to deliver live pups at term. Delay in PTB was associated with reduced feto-maternal uterine inflammation (immune cell infiltration and histologic chorioamnionitis, NF-κB activation, and proinflammatory cytokine production). Conclusions eIL-10 administration was safe, stable, specific, delayed PTB by over 72 hrs and delivered live pups. The delivery of drugs using EVs overcomes the limitations of in-utero fetal interventions. Protecting IL-10 in EVs eliminates the need for the amniotic administration of recombinant IL-10 for its efficacy.